MODELS OF COMMUNICATION STRATEGY IN CONNECTION WITH THE DISTRIBUTION POLICY IN THE FOOD INDUSTRY - DYBCHUK, Liudmyla (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines models of communication strategy in relation to the distribution policy of medium-sized enterprises in the food industry. The relevance of the research is determined by the intensifying competition in domestic and international markets, the digitalization of the business environment, and the need to ensure a stable presence of enterprises within distribution channels. The purpose of the study is to define the principles and mechanisms for building an effective communication strategy that is synchronized with logistical processes and contributes to improving the performance of distribution policy. The methodological basis of the research includes analysis, synthesis, comparison, and systematic generalization. The proposed models take into account the specific features of medium-sized enterprises in the food industry and their resource limitations. They include a sequence of stages ranging from goal setting, identification of target audiences, and the formulation of central messages to the selection of optimal communication channels, integration of online and offline tools, and implementation of performance control mechanisms. Particular attention is paid to the role of digital platforms, CRM systems, and targeted advertising instruments in strengthening communication with consumers and partners. The findings demonstrate that the developed models enhance the effectiveness of communication interactions, ensure consistency between marketing and logistics decisions, and promote the establishment of sustainable partnerships within both B2B and B2C segments. In addition, they contribute to increasing consumer trust, optimizing distribution costs, and improving brand recognition. The practical significance of the research lies in the possibility of applying the proposed models in the activities of Ukrainian food industry enterprises. Their implementation may serve as a foundation for the development of strategic and tactical programs, improving business processes, and strengthening competitive advantages in both domestic and international markets.